Entrepreneurial Potential of Russian society: Analysis and Recommendations to Encourage Involving the Population into the Small Business - Александр Юльевич Чепуренко (Journal of Economic Sociology, 2010)
See the beginning in T. 4 №2, 2003. In the final part of the paper the factors of transition from proto-entrepreneurial to the real entrepreneurial activity are considered. The motivation peculiarities, forms of participation and sources of the capital for beginners are under focus. Moreover the author pays attention to the difficulties to start small and family business basing on a) current and former entrepreneurs, b) experts. The role of service organizations in supporting the start-ups is also under consideration in the paper.